Synthesis of four bar slider mechanism for finitely three separated positions - Ali Mokhtar, Mohd Najib; Wong, Kian Loon; Saleman, Abdul Rafeq; Bani Hashim, Ahmad Yusairi; Jafar, Fairul Azni; Zakaria, Muhammad Zulfattah (Trans Tech Publications, 2014)
Movement of the heliostat tracking sun is able to achieve through simple four bar mechanism. Design methods for four bar linkage encompass a mathematical approach, trial and error method, function generation, motion synthesis and path synthesis. The paper presents a study of motion synthesis of four bar slider mechanism applies to heliostat movement. Mathematical equations used for the synthesis are presented and the results are compared with the graphical method. Procedure of various methods to determine the length and position of the links in case of desired positions of the coupler are presented. As a conclusion, both methods are able to achieve wanted results with an acceptable degree of accuracy. However, the graphical method is helpful to provide better insight of the system during designing the solution compared to the mathematical method.